Precision mapping of schistosomiasis and soil-transmitted helminthiasis among school age children at the coastal region, Kenya. - Stella Kepha; Duncan Ochol; Florence Wakesho; Wyckliff Omondi; Sammy M Njenga; Kariuki Njaanake; Jimmy Kihara; Stephen Mwatha; Chrisistosom Kanyi; Joseph Otieno Oloo; Paul Kibati; Elodie Yard; et al. (Public Library of Science (PLoS), 2023)
Background Accurate mapping of schistosomiasis (SCH) and soil transmitted helminths (STH) is a prerequisite for effective implementation of the control and elimination interventions. A precision mapping protocol was developed and implemented in the coastal region of Kenya by applying the current World Health Organization (WHO) mapping guide at a much lower administrative level (ward). Methods A two-stage cluster survey design was undertaken, with 5 villages in each ward selected. From within each village 50 households were randomly selected, and a single child between the ages of 8 and 14 sampled following appropriate assent. The prevalence and intensity of infection of Schistosoma mansoni and STH were determined using the Kato-Katz method (single stool, duplicate slides) and urine filtration for S. haematobium. Results Of the 27,850 school age children sampled, 6.9% were infected with at least one Schistosoma species, with S. haematobium being the most common 6.1% (95% CI: 3.1-11.9), and Tana River County having highest prevalence 19.6% (95% CI: 11.6-31.3). Prevalence of any STH infection was 5.8% (95% CI: 3.7-8.9), with Lamu County having the highest prevalence at 11.9% (95% CI: 10.0-14.1). The most prevalent STH species in the region was Trichuris trichiura at 3.1% (95% CI: 2.0-4.8). According to the WHO threshold for MDA implementation, 31 wards (in 15 sub-Counties) had a prevalence of ≥10% for SCH and thus qualify for annual MDA of all age groups from 2 years old. On the other hand, using the stricter Kenya BTS MDA threshold of ≥2%, 72 wards (in 17 sub-Counties) qualified for MDA and were targeted for treatment in 2021. Conclusions The precision mapping at the ward level demonstrated the variations of schistosomiasis prevalence and endemicity by ward even within the same sub-counties. The data collected will be utilized by the Kenyan Ministry of Health to improve targeting.